Earthquake Source and Seismic Strain Rate: Portugal in the Context of The Western Part of the Eurasia - Africa Plate Boundary - Borges, JF (2012)
Fault plane solutions, stress-pattern and deformation rate along the Western part of the Eurasia-Africa Plate Boundary, particu- larly between Azores triple junction and Gibraltar are analyzed. A selection of shallow depth seismic events (1.9 = M = 8.0) occurred in the period 1900-2003 have been carefully checked and analysed. The distribution of the focal mechanisms have been analysed by means of different techniques, projections and graphic representations. Seismic moment tensors, moment rate, slip velocity and b values have been estimated. Based on these results, we propose the following: 1) Between the Azores triple junction and Terceira island predominates strike- slip motion with nodal planes trending NNW-SSE and ENW-SSE; between the Terceira island and the beginning of the of Gloria fault the normal mechanisms predominate with nodal plans in the direction of islands. Deformation rate in both regions is 7.4 and 2.4 cm/year respectively. 2) In the continuation of the plate boundary, along the Gloria Fault until the Iberian continental margin we clearly have right-lateral motion in the E-W direction with a deformation rate of 1.8 cm/year. 3) The Eastern part of the Plate boundary, in Portugal continental, is very complex, however we identify some important patterns in the following regions: western Iberian margin (strike-slip), Lisboa and Vale do Tejo (dip-slip), ...vora and vicinity (strike-slip), region of Algarve (strike-slip) and inter-plates boundary zone (inverse). These regions are affected by compression oriented and a deformation rate of 0,55 cm/year.